Implementasi metode bagian dalam meningkatkan keterampilan servis forehand tenis meja - Effendy, Dedy; Sari, Merlina; Fernando, Ricky; Muspita (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2020)
The aim of this research is to improve students' table tennis forehand service skills. This research is a classroom action research. More specifically, this research is collaborative classroom action research, namely collaboration between researchers and field practitioners (teachers). This study consisted of several cycles, each cycle through stages, action planning, action implementation, observation and reflection. The subjects of this study were 27 students of class VIII1 SMP Muhammadiyah 2 Pekanbaru. This study used learning tools and data collection instruments for the performance rubric of table tennis forehand service skills. Based on the results of research and discussion, it can be concluded that the application of the part method can improve the table tennis forehand service skills of class VIII1 students of SMP Muhammadiyah 2 Pekanbaru. Where from 27 students have shown good results where an increase in the number of children who are able to reach or pass the minimum benchmark reference value (KKM). Based on the findings of this study, it is hoped that physical education teachers can make the method part of a solution in improving table tennis forehand service skills.